Immunocytochemical examination of Akt, mTOR, and Pax-2 for endometrial carcinoma through thin-layer endometrial cytology - Ke Ma; Ke Ma; Xi Yang; Xi Yang; Zihui Yang; Yiting Meng; Jia Wen; Jia Wen; Rui Chen; Rui Chen; Jianghui Yang; Qinping Liao; et al. (Frontiers in Medicine)
ObjectiveThis study aimed to detect the expression of Akt, mTOR, and Pax-2 in differing endometrial tissue/cells, together with assessment of such molecular markers for improving accuracy within endometrial cytology screening for endometrial cancer (EC).MethodsOverall, 92 hysteroscopy cases were included. This cohort comprised 32 endometrial carcinoma patients, 30 benign lesion patients, and 30 cases with normal endometrium. Endometrial cells were collected before hysteroscopy, for immunohistochemical (IHC) and immunocytochemical (ICC) detection of Akt, mTOR, and Pax-2. Expression levels were evaluated by semi-quantitative method, and ROC curves (Receiver Operating Characteristic Curve) were drawn to evaluate the application importance for all three biomarkers for EC diagnostics.ResultsIHC expression of Akt, mTOR, and Pax-2 was positively correlated with ICC expression within the endometrial carcinoma cohort, benign lesion cohort, and normal cohort. Using IHC and ICC, Akt/mTOR-marked upregulation was observed within the EC cohort, compared to all other cohorts. Pax-2 was also markedly upregulated within normal/benign lesion cohorts in comparison to the EC cohort (p < 0.01). The sensitivity and specificity of ICC was 73.33 and 91.53%, respectively, when Akt ≥ 190 was used as the diagnostic index for EC. When mTOR ≥ 255 was used as the diagnostic index for EC, such parameters were 84.38 and 95.00%, respectively. When Pax-2 ≤ 165 was used as the diagnostic index for EC, such parameters were 96.67 and 80.00%, respectively.ConclusionThis investigation probed varying threshold levels pertaining to Akt, mTOR, and Pax-2, consequently assisting in endometrial lesion-type identification. IHC within ECT (endometrial cytology test) analyses for Akt, mTOR, and Pax-2 could enhance the capacity for diagnosing EC/pre-malignant lesions.